The facilitators and barriers to physical activity scale for people with mental illness in Taiwan: development and validation. Issue 17 (14th August 2022) - Chen, Ming-De; I, Jung-Hsuan; Pellegrini, Christine A.; Chen, Hui-Fang; Su, Chwen-Yng; Chang, Yen-Ching
Abstract: Purpose: The purposes of this study were to develop a new measure, the Facilitators and Barriers to Physical Activity Scale for People with Mental Illness (FBPAS-MI) and to validate the psychometrics. Methods: This study included two phases. In Phase I, a literature review and five focus groups were conducted to develop an item bank. Then, expert consultation and cognitive interviews were used for content validity. In Phase II, 147 participants with severe mental illness were recruited from 10 community-based psychiatric rehabilitation centers in Taiwan to examine the psychometrics. Principal axis factoring method with direct oblique rotation was used to identify the underlying constructs of FBPAS-MI. Concurrent validity, internal consistency and test-retest reliability were examined. Results: The results revealed five domains in the facilitator subscale (15 items) and two domains in the barrier subscale (11 items). Both subscales showed satisfactory internal consistency (all Cronbach's α >0.80); the concurrent validity and test-retest reliability were established. Conclusions and implications of practice: This study confirmed that the FBPAS-MI is a valid and reliable scale to understand perceived facilitators and barriers to physical activity for severe mental illness. The FBPAS-MI can provide useful information in the development of individualized health promotion program for this population. Implications for Rehabilitation: The Facilitators and Barriers to Physical Activity Scale for People with Mental Illness (i.e., FBPAS-MI) is a valid and reliable assessment to examine key factors affecting physical activity participation among people with severe mental illness. Psychiatric rehabilitation practitioners could use the FBPAS-MI to help develop and tailor individualized physical activity promotion programs based on identified facilitators and barriers to activity.